Rivalry as Synergy? The Japanese Automobile Companies' Export Expansion - Hanssens, Dominique M.; Johansson, Johny K. (Journal of International Business Studies, 1991)
The paper explores “rivalry” and “synergy” arguments to explain the export growth of Japanese auto manufacturers. Previous literature on competitive behavior, including Porter's [1985] discussion of “good” versus “bad” competitors, is used to develop a conceptual framework and empirical methodology to separate out alternative explanations for the Japanese success. Data on Japanese auto companies' sales in six different export markets (Europe, North America, Latin America, Asia, the Middle East and Africa) are examined for the period 1959-1987. The sales over the period are decomposed into three multiplicative components: a generic market growth factor, a synergy factor depicting the combined growth for the Japanese cars, and a rivalry factor representing competition within the Japanese strategic group. The data are used to estimate the magnitude of the growth elasticities for each of the three components.